Pesticide exposure and ocular toxicity - Laquatra, Joseph (Archives of Community Medicine and Public Health, 2020)
Pesticide residues accumulate in homes with higher amounts that are found in the Child Breathing Zone. Negative health effects are known to exist from exposure to pesticide residues, including ocular toxicity. This paper reports on a study of pesticide residues found in a random sample of 132 homes in non-metropolitan counties of New York State. Fifteen pesticides were tested for and residues from all fifteen pesticides were found in all 132 homes. Potential consequences of human exposure to these residues are discussed as is a potential remedy.